2013
DOI: 10.1523/jneurosci.1783-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Cochlear Synaptopathy: An Early-Onset Contributor to Auditory Functional Decline

Abstract: Aging listeners experience greater difficulty understanding speech in adverse listening conditions and exhibit degraded temporal resolution, even when audiometric thresholds are normal. When threshold evidence for peripheral involvement is lacking, central and cognitive factors are often cited as underlying performance declines. However, previous work has uncovered widespread loss of cochlear afferent synapses and progressive cochlear nerve degeneration in noise-exposed ears with recovered thresholds and no ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

79
756
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(844 citation statements)
references
References 72 publications
79
756
2
7
Order By: Relevance
“…We then fixed the tissue and stained for myosin VIIA, a commonly used immunochemical marker that is specifically expressed in HCs. [28][29][30][31][32] We consistently observed tdTomato-negative (dead) HCs that showed immunoreactivity for myosin VIIA ( Figure 6a). As our data indicate that loss of tdTomato is a reliable indicator of HC death, these tdTomato-negative/ myosin VIIA-positive HCs are corpses.…”
Section: Scs Constrict and Remove Hcs Killed By Neomycinmentioning
confidence: 77%
“…We then fixed the tissue and stained for myosin VIIA, a commonly used immunochemical marker that is specifically expressed in HCs. [28][29][30][31][32] We consistently observed tdTomato-negative (dead) HCs that showed immunoreactivity for myosin VIIA ( Figure 6a). As our data indicate that loss of tdTomato is a reliable indicator of HC death, these tdTomato-negative/ myosin VIIA-positive HCs are corpses.…”
Section: Scs Constrict and Remove Hcs Killed By Neomycinmentioning
confidence: 77%
“…This suggests that ABR thresholds are largely independent of wave amplitudes and reflect only the minimum response rather than predicting the maximum capacity to respond. A recent study has also shown the reduction in ABR wave amplitudes with age, corresponding to the loss of synaptic strength in the auditory nerve and the number of spiral ganglion cells, much prior to changes seen in hearing thresholds (Sergeyenko et al 2013). Hence, the thresholds, which measure the lowest detectable level of activity, seem to be indicative of the sensitivity of level coding and detection of sound, while the ABR wave amplitudes, especially at peak response level, seem to be indicative of the number and synchronicity of the neurons in effectively representing these phasic stimuli at their highest capacity.…”
Section: Discussionmentioning
confidence: 93%
“…The ABR thresholds are an indicator of sound sensitivity, outer hair cell function, and the presence of a minimal number of functional auditory nerve synapses (Boettcher 2002;Kujawa and Liberman 2009;KonradMartin et al 2012). The ABR wave amplitudes are an indicator of overall auditory neuronal number and short-term synchrony of each generator and are a better predictor of peripheral synaptic function than ABR thresholds (Kujawa and Liberman 2009;Sergeyenko et al 2013). The FFRs and EFRs are an indicator of sustained temporal processing, emphasizing the functions of more central generators (Kuwada et al 2002;Parthasarathy and Bartlett 2012), given a normal or altered number of hair cells and ribbon synapses, and have been observed to be better predictors of speech perception in quiet and in noise (Anderson et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in healthy animals reared in silence, presbycusis is still observed (Sergeyenko et al 2013;Yan et al 2013).…”
Section: Hearing Neuronsmentioning
confidence: 99%